Synthesis, Characterization and Electrochemical Studies of 2-Amino-4-Phenylthioazole based Azo Dyes - H. Kusuma, P.; Keerthikumar, C. T.; Ramyakumari, C. T.; Raghavendra, T. M. (Journal of Scientific Research, 2025)
The present work outlines the synthesis and characterization of heterocyclic azo dyes derived from 2-amino-4-phenylthiazole through the diazo coupling process. The coupling compounds were 4-hydroxycoumarin, 2,4-dihydroxybenzophenone, and 2-hydroxy-4-methoxy benzophenone. The synthesis was carried out under optimal experimental conditions at temperatures between 0 °C and 0.5 °C, reddish, reddish-orange, and reddish-yellow colors in good yields (50–75 %), they were characterized using various spectroscopic techniques like FT-IR all synthesized compounds exhibited characteristic azo group peaks in the range of 1400–1490 cm⁻¹. The UV-visible spectra were recorded in solvents such as DMSO, ethanol, and acetone. ¹H-NMR spectra OH groups in the compounds were observed at specific chemical shifts: A1 at 12.569 ppm, A2 at 12.223 and 10.850 ppm, and A3 at 12.092 ppm. The ¹³C-NMR spectra to identify carbon environments and further validate the molecular structure. The mass spectra of the compounds showed [m+1] ionic peaks corresponding to their molecular weights confirming the formation of the azo dyes. The electrochemical behavior of the azo compounds was studied using a glassy carbon electrode (GCE) in a 0.1M H2SO4 solution. The study investigated the effect of scan rates (50–250 mV/s) and concentrations (10–50 µM) on the redox properties of the compounds. Irreversible process of the azo center underwent an irreversible reduction involving the consumption of four electrons.